Decoding the Virus: Blending Patterns behind the Name “SARS-CoV-2” (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The disruptive impact of the SARS-CoV-2 pandemic raised awareness of the need for elucidation of its’ conceptual framework among contemporary linguists. This paper attempts to reconstruct the most fundamental conceptual relations within the compound “SARS-CoV-2” in terms of the Conceptual Blending. The main hypothesis for this research states that certain compression patterns and the structural specificity of the emerging blend make the compound “SARS-CoV-2” an efficient conceptual and formal template for multi-scope blending in future linguistic research concerning mutations of the coronavirus. The topology of mental spaces, the emergent structure within the blend, main compression patterns emerging from specific contextual constraints, the interplay of various vital relations, the dynamics of change and the potential to scale down vital relations (transmissibility and transmission dynamics of the SARS-CoV-2 virus) will be outlined. A seven-space-model of the SARS-CoV-2 conceptual integration network will be proposed. The results of analysis of intra- and outer-spatial vital relations connecting the input spaces and respective compression patterns will be demonstrated with reference to similarities and differences between SARS-CoV and SARS-CoV-2.